Force-length properties of leg extension and their implications for strength diagnostics - Hahn, D. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The aim of this study was to identify the F-l-r of multiarticular leg extension and its relation to muscle function. For that purpose, external forces and kinematics of lower extremity were measured (n = 18) during maximum voluntary isometric contractions in a seated leg press. Range of Motion was 30° - 100° knee flexion and measurements were done in steps of 10°. In addition, net joint moments for hip, knee, and ankle joint were computed by inverse-dynamic modelling. With increasing knee flexion one-legged maximal external force (Fext) decreased significantly from 3369±575 N to 1015±152 N, whereas passive forces only had a minor influence. Moreover, correlations showed that above average Fext at low knee flexion is not necessarily associated with above-average Fext at great knee flexion and vice versa. Similarly, it is not possible to simply deduce high joint moments for all joints from high Fext, just as above-average joint moments in one joint don`t implicitly signify above-average joint moments in another joint. In conclusion, these results show that the diagnosis and interpretation of leg extension strength in terms of muscle function via external forces must be done with extreme caution.